Centro de Beneficio e Industrialización de los Productos y Subproductos Derivados del Café, en el Municipio de Hobo – Huila (2021)
In this research project, the municipality of Hobo-Huila is mainly studied, since it presents a problem that the coffee union has suffered throughout the Colombian country for many years, due to the low purchase price of the coffee load and the high costs of production, since the sustainability of the crops is affected by the high prices of inputs and the direct cost of labor in the harvesting process. For this reason, the behavior originated by coffee producers to seek good purchase prices is mainly examined, since management occurs through informal trade referred to small traders who are governed by the price stipulated by cooperatives. that preside over the commerce of the Huila region. Taking into account the problems caused by the low cost of purchasing coffee, research is being carried out on products and by-products derived from coffee, since nowadays in small parts of the country it is used only in an artisanal way. It concludes by proposing industrialization strategies to solve the problem; good coffee practices through process unification; model in the industrial field through architectural environments; contemplate the relationship of spaces between the handling, processing, and industrialization of coffee.